Laser Ablation-Inductively Coupled Plasma-Mass Spectrometry (LA-ICP-MS) Mapping of Element Distribution in Leaves of Wheat Colonized by Intact Arbuscular Mycorrhiza Extraradical Mycelium - Faria, J. M. S. (2022)
Abstract: In acidic soils with Mn toxicity, the development of an intact arbuscular mycorrhiza extraradical mycelium (ERM) by stress-adapted native plants can promote increased growth and protection against metal toxicity, in subsequent crops. In a recent study, the growth of Ornithopus compressus (ORN) in acidic soil doubled shoot weight, increased P contents and decreased shoot Mn in successive wheat crops. The biochemical mechanisms involved in this beneficial effect may include the subcellular redistribution of nutrients and of excess Mn. In the present work, shoot Ca, Fe, Mg, Mn, P, K, Si, Na and Zn were mapped through Laser Ablation-Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS), in wheat grown for 3 weeks in undisturbed soil, where ORN previously developed an extensive ERM network. Element mapping allowed for the detection of higher levels of Fe, Mg, Mn, P, K, Na and Zn in the interveinal sections of wheat leaves while Ca and Si showed higher levels in vascular zones of the adaxial side. This preliminary work is part of an ongoing project which aims at identifying biochemical mechanisms responsible for the protective properties of an early AM colonization of crops, by ERM previously developed in association with native plants under Mn toxicity. Future research will determine the subcellular redistribution of these elements and excess Mn.